Demographics and viability of an estuarine community of Indo‐Pacific bottlenose dolphins. Issue 1 (16th August 2022) - Nicholson, Krista; van Aswegen, Martin; Loneragan, Neil; Bejder, Lars
Abstract: Wildlife management requires reliable demographic information to assess the status of a population and its vulnerability to threats. This study calculated age class‐ and sex‐specific demographic parameters and assessed the viability of a community of Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) resident to the Peel‐Harvey Estuary in Western Australia. Boat‐based photo‐identification surveys ( n = 483) were conducted between 2016 and 2019. A population viability analysis (PVA) was used to assess the community status and evaluate the effects of adult female and calf mortality, and reproduction on population growth rate. The community comprised 88 ( SD = 4.43) individuals with a sex ratio close to parity in all but the adult age class where it was skewed towards females. Demographic changes in this community are driven by births, deaths, and the likely permanent emigration of juvenile males. No immigration was observed. The population is stable ( r = −0.004, SD = 0.062) given the current demographic rates. To maintain a community of ~90 individuals, management should consider action to lower adult female and calf mortality. This should involve aiming for zero human caused mortality and ensuring adverse impacts to the population are considered in future development planning.